International finance: the National Advisory Council on International Monetary and Financial Policies annual report to the President and the Congress for fiscal year 1984 (Washington D.C.: The Secretary of the Treasury, 1985)
This report includes an account of the United States participation in the International Monetary Find and the multilateral development banks, together with related data and material concerning the operations and policies of the Fund and the banks
osc 12/04/2019
Loans
Keywords: International finance; Finance